ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING DAN PENENTUAN HARGA JUAL BERBASIS COST PLUS PRICING SERTA TINJAUAN MARKETING MIX (Studi Kasus pada Konveksi Kharisma Abadi Kota Surakarta) - Kharismatun Khoiriyah; Ahmad Husin; Dwinda Agustintia (ITB AAS Indonesia Surakarta, 2025)
Abstract This study aims to analyze the calculation of cost of goods manufactured using the full costing method and determine the selling price using the cost plus pricing method at Konveksi Kharisma Abadi in Surakarta. A quantitative descriptive approach was used, with data collected through interviews, observations, and documentation. The findings indicate that the full costing method provides a more accurate cost structure compared to the company’s existing method. Applying cost plus pricing results in a selling price that reflects appropriate profit margins. Additionally, the marketing mix strategy including product, price, place, and promotion supports effective pricing decisions. The integration of full costing and marketing strategies enhances operational efficiency and business competitiveness. Keywords: Full Costing, Cost Plus Pricing, Cost of Goods Manufactured, Selling Price, Marketing Mix.